2005
DOI: 10.1088/0953-4075/38/14/014
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurements of shifts and asymmetries of He II Pαand Pβspectral lines

Abstract: Red shifts and asymmetries of He II Pα 468.5682 nm and Pβ 320.3104 nm lines were measured in a pulsed plasma at an electron density measured by two-wavelength interferometry which ranges from 5.54 × 1022 m−3 to 7.48 × 1022 m−3 with uncertainty of 10%. Temperature ranges from 1.70 to 1.83 eV, and has been determined from intensities ratio of Pα and Pβ lines. Shifts for these lines were obtained using as reference lines Cd I 467.8149 nm and He I 318.7745 nm respectively. Measurements of asymmetries have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The spectroscopic beam was limited by two diaphragms (D1, D2) 3 mm in diameter, and focused by a concave mirror ( M6) of 150 mm focal length onto the entrance slit (70 m width) of a Jobin-Yvon monochromator (1.5 m focal length, 2400 lines mm À1 holographic grating). The positions and diameters of diaphragms D1 and D2 ensure the observation of a homogeneous part of the plasma with variations in n e and T e less than 5% (Peláez et al 2005), due to the high cylindrical symmetry observed in the electron density and temperature spatial distributions .…”
Section: à3mentioning
confidence: 99%
See 1 more Smart Citation
“…The spectroscopic beam was limited by two diaphragms (D1, D2) 3 mm in diameter, and focused by a concave mirror ( M6) of 150 mm focal length onto the entrance slit (70 m width) of a Jobin-Yvon monochromator (1.5 m focal length, 2400 lines mm À1 holographic grating). The positions and diameters of diaphragms D1 and D2 ensure the observation of a homogeneous part of the plasma with variations in n e and T e less than 5% (Peláez et al 2005), due to the high cylindrical symmetry observed in the electron density and temperature spatial distributions .…”
Section: à3mentioning
confidence: 99%
“…All measurements were performed in second-order diffraction, with an exposure time of 5 s. In this configuration, the spectrometer has an inverse linear dispersion of 2.27 pm per channel at 295.0 nm and 1.8 pm per channel at 339.0 nm, with an uncertainty of about 0.6% (Peláez et al 2005).…”
Section: à3mentioning
confidence: 99%
“…The algorithm used to obtain isolated profiles for these lines has been extensively explained in previous works (Rodríguez et al 2003;Peláez et al 2005). In our work, differences between experimental profiles and best fits are lower than 10%.…”
Section: Data Treatment Results and Discussionmentioning
confidence: 99%
“…Therefore, these broadening mechanisms are shown to be negligible for this spectral line and these plasma conditions. To estimate shift, as in previous works (Peláez et al 2005), it was assumed that the centre of the line is the average of the middle points at heights between 25% and 75% of the maximum intensity. In order to obtain the relative shift, centres of He I 318.8 nm lines for different instants along the plasma life were fitted to a straight line, which takes null value when the electron density is zero.…”
Section: Data Treatment Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation